1998
DOI: 10.1007/bf02761143
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1-β, tumor necrosis factor-α, insulin secretion and oral glucose tolerance in non-diabetic siblings of children with IDDM

Abstract: Recent reports suggest that the pancreas participates in tumor necrosis factor alpha (TNF-A) production during stress, and that the islets are predominantly responsible for such synthesis. In vitro TNF-A and interleukin 1-beta (IL-1-beta) inhibit insulin release from islet beta-cells. We measured the circulating levels of IL-1-beta, TNF-A and islet cell antibody (ICA) in 30 children with IDDM (10 of them at their first presentation), 30 of their non-diabetic siblings, and 30 normal age-matched children. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The use of carvedilol in this study was in line with the Food and Drug Administration (FDA) regulations stipulating that a drug can be used off label in the practice of medicine [31,32].…”
Section: Methodsmentioning
confidence: 75%
“…The use of carvedilol in this study was in line with the Food and Drug Administration (FDA) regulations stipulating that a drug can be used off label in the practice of medicine [31,32].…”
Section: Methodsmentioning
confidence: 75%
“…TNFα is suggested to mediate damage to microvascular and macrovascular tissues, to alter insulin secretion and glucose homeostasis (43,44). However, in previous studies results of measuring TNFα levels are reported to be increased (15,19) in patients with diabetes, decreased (20), or not different (21,22). The IL-2 system is known to be associated with autoimmune processes and therefore with T1DM, too.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies found an increase in serum IL‐6 levels in patients with T1DM , whereas others found no difference . Results of measuring TNFα levels are also reported to be increased in patients with diabetes, decreased or not different either . Investigations of serum levels of IL‐10 in diabetic patients are even rarer.…”
mentioning
confidence: 99%
“…TNF-␣ is associated with the initiation and progression of both major forms of diabetes (6,42,(67)(68)(69)(70). Indeed, TNF-␣ has been shown to have direct cytotoxic effects on ␤ cells and inhibit insulin secretion (4,60,(71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%